INTERNATO REGIONAL: PERCEPÇÃO DO ACADÊMICO DE MEDICINA SOBRE SEU IMPACTO NA FORMAÇÃO MÉDICA - GARNES, Giulia Candida Ribeiro; PRATA, Lucas Ferreira; SANTOS, Mirella Ferreira da Cunha (ANAIS DO ENIC, 2022)
-